Modes of Teacher Participation in the Digitalization of School - Lone Dirckinck-Holmfeld; Bertil Johannes Ipsen; Andreas Lindenskov Tamborg; Jonas Dreyøe; Benjamin Brink Allsopp; Morten Misfeldt (Stockholm University Press, 2019)
Previous research has emphasized the importance and potential of actively involving teachers in the design and implementation of educational technologies in schools. However, only a few studies have explored the development of methodologies for engaging teachers in the appropriation of digital technologies, as the increased digitalization of many education sectors demands. Drawing on experiences from two large-scale participatory research projects, this paper investigates two approaches to involving teachers in the design and implementation of digital learning platforms. Specifically, the paper draws on case examples to examine how participatory data design and future workshops can help to cultivate communities of practice in support of teachers' appropriation of digital technologies.